(untitled) (Philological Studies, 2019)
The description of the city language situation implies taking into consideration such phenomenon as a human. The statistic analysis used in the article aims at revealing factors influencing the usage of phonetic, lexical and syntactic units in the speech practice of the city dwellers. As a result the hierarchy of socio-, bio- and psychological factors (such as birthplace, education, profession, age, gender, character) determining the speaker speech behaviour is defined.